7x-3-2x=2(x+3)
5x - 3 = 2x + 6
3x = 9
x = 3
2006-12-11 23:10:00
·
answer #1
·
answered by anton3s 3
·
0⤊
0⤋
7x - 3 - 2x = 2(x + 3)
5x - 3 = 2x + 6
5x - 3 - 2x = 2x + 6 - 2x
3x - 3 = 6
3x - 3 + 3 = 6 + 3
3x = 9
3x / 3 = 9 / 3
x = 3
The answer is x = 3
Insert the x value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
7x - 3 - 2x = 2(x + 3)
7(3) - 3 - 2(3) = 2(3 + 3)
21 - 3 - 6 = 2(6)
21 - 9 = 12
12 = 12
- - - - - - s-
2006-12-11 23:19:09
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
I'm not too happy solving maths trivia like yours, but for the sake of 2 points, here you are:
7x - 3 - 2x = 2x + 6
5x - 2x = 6 + 3
3x = 9
x = 3
2006-12-11 23:13:33
·
answer #3
·
answered by Paleologus 3
·
0⤊
0⤋
Aww, come on.
If you are still in school, you should have more brains that half the people here!
Do your own homework!
That said, I can't resist a simple math equation.
7x-3-2x=2(x+3)
5x-2x=6+3
x=9/3=3
2006-12-11 23:16:03
·
answer #4
·
answered by xxon_23 7
·
0⤊
0⤋
7x-3-2x=2(x+3)
5x-3=2x+6
5x-3-2x=2x-2x+6
3x-3=6
3x-3+3=6+3
3x=9
x=3
That is showing your work, oppose to just the answer by the way!
2006-12-11 23:12:44
·
answer #5
·
answered by ? 1
·
1⤊
0⤋
develop
7x-3-2x = 2x+6
5x-3 = 2x+6
3x=9
x=3
it works . both side are 12
2006-12-11 23:26:56
·
answer #6
·
answered by maussy 7
·
0⤊
0⤋
7x-3-2x=2(x+3)
7x-3-2x=2x+6
7x-2x-2x=6+3
3x=9
x=3
2006-12-11 23:53:07
·
answer #7
·
answered by Saphira 3
·
0⤊
0⤋
7x-3-2x=2x+6
5x-3=2x+6
5x-2x=6+3
3x=9
x=9/3
x=3
:)
2006-12-11 23:25:37
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋